Production of extracellular adenosine by CD73+ dendritic cells is crucial for induction of tolerance in contact hypersensitivity reactions - Silva-Vilches, Cinthia; Ring, Sabine; Enk, Alexander; Mahnke, Karsten (The journal of investigative dermatology, 2019)
Dendritic cells (DCs) express the ecto-5′-nucleotidase CD73 that generates immunosuppressive adenosine (Ado) by dephosphorylation of extracellular Ado monophosphate and diphosphate. To investigate whether CD73-derived Ado has immune-suppressive activity, 2,4-dinitrothiocyanobenzene (DNTB) was applied to skin of wild-type (WT) or CD73-deficient (CD73-/-) mice, followed by sensitization and challenge with 2,4-dinitrofluorobenzene. In this model, we show the induction of tolerance by DNTB against 2,4-dinitrofluorobenzene only in WT but not in CD73-/- mice. Analysis of skin DCs showed increased expression of CD73 after application of DNTB in WT mice. That was accompanied by elevated concentrations of extracellular Ado in the lymph node. Moreover, T cells expressed markers for anergy, namely EGR2 and NDRG1 in DNTB-treated WT mice and they exhibited impaired proliferation upon ex vivo re-stimulation. Similarly, in vitro we observed that Ado-producing WT DCs, but not CD73-/- DCs, rendered transgenic T cells from OTII mice (OTII T cells) hyporeactive, decreased their T-cell costimulatory signaling, and induced up-regulation of EGR2 and NDRG1. Thus, these data show that expression of CD73 by DCs, which triggers elevated levels of extracellular Ado, is a crucial mechanism for the induction of anergic T cells and tolerance.
Published online 28 October 2018; corrected proof published online 12 January 2019
Gesehen am 04.09.2019